Lightning Risk Mapping in West Sumatra using Kernel Density Estimation and Simple Additive Weighting - Hardika, Deny; Eka Fauzy, Muhammad Alvy; Samidi, Samidi (Sistemasi: Jurnal Sistem Informasi, 2025)
This study analyzes the spatial distribution, occurrence frequency, and lightning hazard vulnerability levels in West Sumatra during March 2024 using a geospatial and multi-criteria approach. By integrating meteorological data with land vulnerability assessments, the research applies Kernel Density Estimation (KDE) to map lightning strike density and employs Simple Additive Weighting (SAW) to incorporate land cover and socio-economic factors into the vulnerability evaluation. This combined approach produces a comprehensive lightning hazard risk map, identifying high-risk zones covering 3.01%, medium-risk zones 21.72%, low-risk zones 25.75%, and safe zones 49.52% of the total area. This innovative methodology represents a significant step forward in improving lightning risk management strategies and disaster mitigation policies, particularly in regions vulnerable to climate change and rapid urbanization. The findings not only highlight the importance of integrating spatial lightning data with environmental vulnerability assessments but also support practical applications in early warning systems and spatial planning to effectively minimize the impact of lightning hazards.